Determinants of Nutritional Rickets among Children Aged below 5 years in Naivasha District Hospital, Kenya - Wangari , Angela; Were , Gertrude (African Journal of Education,Science and Technology (AJEST), 2013)
Rickets, a common deficiency disease affecting children below five years of age , is rare in most developing countries but is observed in severely malnourished children. According to literature, Vitamin D, Calcium and Phosphorus deficiencies are the main causes of rickets. The purpose of this study was to investigate the determinants of the development of nutritional rickets among children below 5 years undergoing treatment at the Naivasha District Hospital (NDH). Out of the target population of one hundred and eighty four children (184), seventy four (74) mother -child pairs were purposively selected for this study. The children in this study had been diagnosed with rickets and were undergoing treatment and occupational therapy at NDH. A structured questionnaire was administered to the caretakers of the children. Two (2) key informants from the Municipal council were interviewed and provided information regarding water quality. A pilot test was conducted before data collection. Data was analyzed using the Statistical Package for Social Sciences (SPSS) version 20 (2011). A p value of >0.05 was considered significant. Results showed that poor feeding practices were evident where children were deprived of animal source proteins represented by forty six percent (46%) in infants and forty percent (40%) among those diagnosed post-infancy. Majority (41%) of the children had inadequate daily sunlight exposure of less than 30 min a day. Fifty nine percent (59%) of them were fully clothed during sunlight exposure. Sixty seven percent (67%) of the households used fluoride contaminated borehole water for cooking activities. This finding was significant (p=0.05). Insufficient sunlight exposure due to inappropriate dressing and use of fluoride contaminated water were the main determinants of rickets among these children. It is hoped that results from this study can be used to develop interventions which can alleviate the prevalence of rickets among children in Naivasha